La profesión desde las antípodas: Australia diseña su futuro en ByD - Gil-Solés, Daniel (Anuario ThinkEPI, 2015)
Reseña del informe:Australian Library and Information AssociationÂ (2014). Future of the library and information science profession. Canberra: ALIA.https://www.alia.org.au/sites/default/files/documents/advocacy/ALIA-Future-of-the-Profession-ALL.pdf